Hasil penyesuaian diri sebagai perantara bagi hubungan sosialisasi organisasi, tingkah laku proaktif dan keterlibatan kerja guru baharu - Rozita, Abdullah (2019)
Teacher engagement is an important element in improving teacher performance and school productivity. Teacher workload, work pressure, work resources and organizational socialization processes are among the factors that influence the behavior and the engagement of teachers. This study was carried out among new teachers, primarily to identify the influence of organizational socialization factors and proactive behaviors on their engagement, whether directly or indirectly through self-adaptation (self-efficacy factors, clarity of role, social acceptance) which are proposed as the mediators. This study uses a quantitative research method which is a survey study involving the testing of structured models. The data were collected through cross sectional through a questionnaire developed based on the instrument that adapted and tested the validity and reliability. The sample was 312 secondary school teachers from eight districts in Kedah. The results of the study showed that gender and teacher work experience are not significant in differentiating the level of organizational socialization, proactive behavior and new teacher engagement; and all study constructs have positive and significant relationships. Model testing also demonstrates self efficacy and social acceptance as significant mediators to explain the indirect influence of organizational socialization factors and proactive behavior towards new teacher engagement. Theoritically, this study provides empirical evidence on the merging of Bandura's Learning Theory and Job Demand Resources Model. Practically, the findings of the study can be used as a guidance for the Ministry of Education in their efforts to improve the quality of the new teacher induction programme by taking into account the socialization of the organization which includes interpersonal relationships, the application of pedagogical skills and the knowledge of teacher career development. The effort will create self-esteem and sense of belonging among school children, thereby enhancing the engagement of new teachers.